PENGARUH LAYOUT, WORD OF MOUTH DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA WARUNK DUREN TULUNGAGUNG - Fadil, Mohammad; Nurzainul Hakimah, Ema; Kurniawan, Rony (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The culinary business is a business that can be developed in the future, because food is one of the basic human needs. The purpose of this study was to determine the effect of layout, word of mouth, and price on purchasing decisions at Warunk Duren Tulungagung. This study uses a quantitative approach using primary and secondary data. The population in this study are people who buy products, with a sample of 40 respondents,, using analysis of validity test, reliability test, classical assumption test, multiple linear regression test, coefficient of determination, t-test and F-test. The results of the study can be concluded that (1)layout has a significant partial effect on purchasing decisions. (2)word of mouth partially significant effect on purchasing decisions. (3)price has a significant effect partially on purchasing decisions. (4)Layout, word of mouth, price simultaneously have a significant effect on purchasing decisions.